The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s11832-009-0177-6
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of the scarf osteotomy in adolescent hallux valgus

Abstract: This study indicates that scarf osteotomy should be used with caution in symptomatic adolescent hallux valgus, as there is a high recurrence rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 26 publications
1
35
1
8
Order By: Relevance
“…In our study, the modified scarf osteotomy could effectively correct the DMAA, restore the matching of metatarsus and toe joints, and reduce the postoperative recurrence rate. Moreover, the addition of Akin osteotomy can increase the corrective abilities of the scarf osteotomy. An additional Akin osteotomy was also performed in our study if hallux valgus deformity was not completely corrected.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In our study, the modified scarf osteotomy could effectively correct the DMAA, restore the matching of metatarsus and toe joints, and reduce the postoperative recurrence rate. Moreover, the addition of Akin osteotomy can increase the corrective abilities of the scarf osteotomy. An additional Akin osteotomy was also performed in our study if hallux valgus deformity was not completely corrected.…”
Section: Discussionmentioning
confidence: 98%
“…A previous study has confirmed that scarf osteotomy has a better corrective ability for hallux valgus deformity compared with the distal metatarsal osteotomy. Moreover, the scarf osteotomy has been suggested to treat adolescent hallux valgus deformity because this surgery allows rotational correction in addition to translation; however, mixed results were obtained from different studies. In detail, John et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean age at the time of surgery was 14.1 years (range 10-17 years). Previous studies have included patients from the age of 9 through to 18 years with comparable mean ages [9][10][11]. These studies have not attempted to differentiate between those patients with an open physis or not, presumably because of the variable age at closure and the difficulty in making this distinction radiographically when closure is occurring.…”
Section: Methodsmentioning
confidence: 99%
“…Пациенты были обследованы до опера-ции, затем через 3, 6 и 12 месяцев после нее. Данная кратность обследования соответствовала реко-мендациям ведущих зарубежных и отечественных клиник [1,4,11]. Для объективизации оценки ре-зультатов хирургического лечения использовали балльную оценочную шкалу, рекомендованную Американским ортопедическим обществом хирур-гии стопы и голеностопного сустава (AOFAS).…”
Section: материал и методыunclassified